Nutritional Status of Mothers of Well-Nourished Children versus Malnourished Children at Civil Hospital Hyderabad - Kailash, Bindia; Shaikh, Salma; Chohan, Muhammad Nadeem; Hanif, Muhammad; Shah, Mushtaque Ali (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To compare the nutritional status by using Body Mass Index (BMI) among Mothers of Well nourished Children versus malnourished children at Civil Hospital Hyderabad METHODOLOGY: A Comparative/ Analytical observational study conducted at paediatric Department, Unit-I, Civil Hospital Hyderabad from March 2015 to February 2016 in total 384 mothers. Group A and Group B, both had 192 mothers. Group A contain mothers of malnourished children (whose mid upper arm circumference was <11.5 cm) and Group B contain mothers of well-nourished children (whose mid upper arm circumference was >12.5 cm). Body Mass Index of mothers were calculated and classified into normal, mild underweight, moderate and sever underweight. RESULTS: BMI of mothers of well-nourished children were better than the BMI of mothers of malnourished children. Around 73.9% mothers of well-nourished children had normal BMI as compared to mothers of malnourished children (10%). Around 18.2% mothers of well-nourished children were mildly underweight comparing 41.1% mothers of malnourished children. Nearly 6.3% mothers of well-nourished children were moderately underweight while 28.9% mothers of malnourished children were moderately underweight. More mothers of malnourished children were severely underweight (20%) as compared to mothers of well-nourished children (1.6%). CONCLUSION: In this study, majority of mothers of children with malnutrition had lower Body Mass Index (Underweight), as compared to mothers of well-nourished children.